Role of Facebook in Covid-19 Crisis Management and Awareness Raising Efforts in Bangladesh: Sentiment And Thematic Analysis - Islam, Md Ashraful (Center for Risk Management & Sustainability and RSF Press, 2022)
The advent of social media opened up a new window of opportunity for crisis communication. These platforms hold great promise as emergency communication tools. It is essential to understand the potential of these platforms in reaching people during an unknown circumstance like the Covid-19 pandemic. This study aims to assess the role of Facebook in Covid-19 awareness-building efforts and its relevance for crisis communication in the public sector of Bangladesh. Posts and comments from the Facebook page of the Directorate General of Health Service (DGHS) were extracted from January 1 to June 8, 2020. Government efforts were classified and categorized by different themes based on the content of the posts made by the DGHS. Citizen response and the effort of the DGHS were evaluated by sentiment analysis on English comments made by Facebook users. The results show that the DGHS actively initiated posts from the first Covid-19 case with a significant increase in citizen engagement over time. Nine significant themes from the content of the DGHS’s post were identified, among which Facebook live bulletin (28%) and awareness and preventive measures (26%) were the most prevalent themes. Sentiment analysis found the prevalence of positive sentiment in over 20% of the comments. The findings suggest that the DGHS significantly draws public attention through the active use of its Facebook page. Through an official source, Facebook played a key role in facilitating emergency communication during the pandemic and delivering awareness campaigns on behalf of the government.